Phytochemical and Bioactive Evaluation of Cissus rotundifolia and Maydis stigma Cultivated in Taiz, Yemen - Mubarak, Ahmed Y.; Almaqtari, Maher A.; Gumaih, Hussein; Alasbahy, Afrah (PSM Biological Research, 2021)
The aim of the study was to investigate antioxidant and antibacterial activity of methanolic leaf extracts of Cissus rotundifolia (CR) and Maydis stigma (corn silk) type Zea mays L from Taiz -Yemen. Phytochemical analysis of Cissus rotundifolia extract indicated the presence of triterpenes, carbohydrates, and/or glycosides, tannins, flavonoids, coumarins, and saponins, and the Maydis stigma (corn silk) type Zea mays L extract indicated the presence of alkaloids triterpenes, carbohydrates, and/or glycosides, tannins, flavonoids, saponins, proteins and free amino acids. The extracts were tested against different bacteria such as Pseudomonas aeruginosa, Proteus and Klebsiella. The methanol extracts of Cissus rotundifolia showed effective free radical scavenging in the DPPH assay.